Dejetos de animais como fertilizante em longo prazo: impacto nas emissões de óxido nitroso e na produtividade das culturas - Bacca, Alessandra (2018)
The application of animal manure in the soil aims to provide nutrients to the plants, especially nitrogen (N). However, areas with a history of applications (over 10 years) may favor the accumulation of N in the residual organic pool, more notably in the most labile. As a result, this can change the dynamics of N and thus influence the availability of N in the soil. However, part of N added by manure can be lost through N2O. In southern Brazil, manure management is one of the main routes of N2O emission. As a greenhouse gas with a high potential for global warming, its emission has been increasingly studied after the use of animal manure. The application history can form a large residual N effect on the soil, which may vary depending on the type of manure. Small quantities of N added by the manure are absorbed by the crops, being mostly originated from the N accumulated in the soil. Thus, these areas may have an even greater potential to emit N2O even after the end of applications, since the rate of mineralization may increase and provide more NO3-. Moreover, the residual effect of N may result in high yields and reach periods when the applied N rates can be reduced and consequently decrease N losses. As a result, this study aimed to evaluate the residual effect of 16 applications of different animal manure and the effect of the continuation of their applications, which totaled 18 applications on N2O emission, productivity and efficiency of N use by black oat and maize crops. To achieve this objective, two studies were conducted in a field with Red Dystrophic Argisol. The experiment has been conducted since 2004 in the soil department of the Federal University of Santa Maria / RS. The results of this work correspond to the period of 2015-2016 with black oat and maize crops. Both studies were conducted simultaneously. The treatments evaluated were Pig slurry (PS), Dairy slurry (DS), Pig deep litter (PL), mineral fertilizer (MF) and a control treatment, which are arranged in a randomized complete block design with four replicates of 5 x 5 m. Before the application of treatments in black oats, a plot of 2 x 2 m was delineated, in which residual effects on black oats and corn were evaluated. The animal manure manure manure was applied normally in the rest of the plot. In study I, the evaluations began one day after the application, where the effect of the continuation of the applications in all the treatments and only the residual effect of the PS and DS treatments was evaluated. In study II, the dry matter (DM), N content in DM, grain yield and N in the grain were also determined, in addition to the efficiency indexes of N use with the continuation of applications and residual effect of all treatments. It was possible to observe in both studies that the application history changed the dynamics of N in the soil. In study I, it was possible to observe higher emissions with the more solid manure, especially the DS with an accumulated annual emission of 13.1 kg ha-1, resulting in an emission factor (EF) of 4%, which is 4 times more than estimated by the Intergovernmental Panel on Climate Change (IPCC). NO3 - levels in the soil were high since the beginning of the evaluations and remained high throughout the period, which justifies the high emissions. Added to this, precipitation influence was related to virtually all emission peaks. The 16 applications showed that even after one year without new applications, the soil still had capacity to emit N2O, especially in the PL treatment that had a cumulative annual emission of 5.8 kg ha-1. In these treatments, NO3 - levels were also high, which shows that applications for several years can significantly change the dynamics of N in the soil where the rates of mineralization are high. In study II, DM productivity, N accumulation and grain yield were higher with the application of DS in black oats and DS and PS in maize. In each culture, the other treatments did not differ from MF in almost all evaluations. Moreover, the residual effect showed that even though there were no more applications during the year, the soil was able to produce N and other nutrients available to the plants, although the yields were not higher when applied. The 18 applications in a sandy soil showed that both crops were able to use N with high efficiency and low losses. Even with emissions with 18 applications of animal manure, they were not higher than emissions with fewer applications.